Persepsi Petani Padi terhadap Perubahan Iklim di Kabupaten Pamekasan - Afifah Azzah Ramdhamayanti; Moh. Wahyudi Priyanto; Mokh. Rum (Ma'soem University, 2026)
Climate change is a global issue that has a direct impact on the agricultural sector, especially on rice commodities. The problem faced is the uneven understanding of rice farmers about the phenomenon of climate change. The purpose of this study was to analyze the perception of rice farmers on climate change in Pamekasan District. This research was conducted from September 2024 using descriptive statistical analysis method. The research data were taken from a research sample of 100 farmers selected using simple random sampling method. The results showed that most farmers are aware of climate change, such as changes in temperature, rainfall, wind speed, shifts in the growing season, and extreme weather that have a direct impact on agricultural productivity. This awareness is an important foundation in shaping adaptive attitudes and behaviors. Therefore, it is expected that by increasing farmers understanding of the phenomenon of climate change, they will be more responsive in dealing with changes in climate conditions and be able to make the right decisions in managing farming in a sustainable manner.